Unmet needs in the transition to adulthood: 18‐ to 30‐year‐old people with hemophilia. (December 2015) - Quon, Doris; Reding, Mark; Guelcher, Chris; Peltier, Skye; Witkop, Michelle; Cutter, Susan; Buranahirun, Cathy; Molter, Don; Jane Frey, Mary; Forsyth, Angela; Tran, Duc (Bobby); Curtis, Randall; et al.
Abstract : Young adults with hemophilia face unique challenges during the transition to adulthood, including issues associated with switching from pediatric to adult hematology care, building mature interpersonal relationships, and establishing an independent career with an assurance of medical insurance coverage. A greater understanding of these challenges is essential for developing effective strategies to address the specific needs of this population. These challenges may be differentiated from those of older adults with hemophilia in large part because of more extensive childhood prophylaxis and safer factor products, resulting in fewer joint problems and lower rates of HIV and HCV infections. This analysis of the changing nature and unmet needs of today's young adults entering into adult hemophilia treatment centers, as well as potential strategies for optimally addressing these needs, was developed following roundtable discussions between patients, caregivers, hematologists, and other health care professionals participating in comprehensive care. Challenges identified among young adults with hemophilia include psychosocial issues related to maturity, personal responsibility, and increased independence, as well as concerns regarding when and with whom to share information about one's hemophilia, limited awareness of educational and financial resources, and a low perceived value of regular hematology care. The initiatives proposed herein highlight important opportunities for health care professionals at pediatric and adult hemophilia treatment centers, as well as national organizations, community groups, and career counselors, to address key unmet needs of this patient population. Am. J. Hematol. 90:S17–22, 2015. © 2015 Wiley Periodicals, Inc.